2012
DOI: 10.1007/s12035-012-8336-z
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes Detected by Ex Vivo High Resolution 1H NMR Spectroscopy in the Striatum of 6-OHDA-Induced Parkinson’s Rat

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder characterized by the progressive loss of the dopaminergic neurons; however, its crucial mechanism of the metabolic changes of neurotransmitters remains ambiguous. The pathological mechanism of PD might involve cerebral metabolism perturbations. In this study, ex vivo proton nuclear magnetic resonance ((1)H NMR) was used to determine the level changes of 13 metabolites in the bilateral striatum of 6-hydroxydopamine (6-OHDA)-induced PD rats. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
3
35
0
1
Order By: Relevance
“…However, extracellular glutamine accumulation was reduced (Figure 4E). Contradictory findings have been reported regarding the changes in levels of glutamate and glutamine in response to these neurotoxins 33,34 or in the serum and cerebrospinal fluid of PD patients. 35,36 Interestingly, despite TCA cycle blockage by paraquat, both TCA cycle metabolites oxoglutarate and succinate remained unchanged.…”
Section: Results and Discusionmentioning
confidence: 99%
“…However, extracellular glutamine accumulation was reduced (Figure 4E). Contradictory findings have been reported regarding the changes in levels of glutamate and glutamine in response to these neurotoxins 33,34 or in the serum and cerebrospinal fluid of PD patients. 35,36 Interestingly, despite TCA cycle blockage by paraquat, both TCA cycle metabolites oxoglutarate and succinate remained unchanged.…”
Section: Results and Discusionmentioning
confidence: 99%
“…One study examined the effect of bilateral 6-hydroxydopamine (6-OHDA) lesions in Sprague-Dawley rats on striatal concentrations of glutamate, glutamine, and GABA measured with 1 H-MRS ex vivo (Gao et al, 2013). Compared to controls, 6-OHDA rats showed increased concentrations of glutamate (1.63 ± 0.24 vs. 1.91 ± 0.1, p = 0.010) and GABA (0.55 ± 0.12 vs. 0.69 ± 0.05, p = 0.009) in the right striatum, as well as a decrease in glutamine (1.37 ± 0.32 vs. 1.13 ± 0.06, p = 0.049).…”
Section: Ex Vivo 1 H-mrs In Rodentsmentioning
confidence: 99%
“…Untargeted metabolomics has been recently applied to PD in order to identify disease biomarkers and for the investigation of drug metabolites resulting from PD treatment [216-220]. Bogdanov et al [216] identified approximately 2000 metabolites in plasma samples obtained from 25 healthy controls and 66 PD patients by using high performance liquid chromatography coupled with electrochemical coulometric array detection (LCECA).…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al [220] used 1D 1 H-NMR spectroscopy and PLS to detect metabolic changes in the striatum of 6-OHDA-induced Parkinson's rat. The right striatum of Sprague–Dawley rats were injected with 1.5 μg/μL of 6-OHDA.…”
Section: Discussionmentioning
confidence: 99%